Theoretical Model of a New Type Tunneling Transistor - Pfeffer, P. (Acta Physica Polonica A, 2023)
A tunneling transistor without heterojunction as a theoretical design, or more precisely, the controlled transmission of an electron current through barrier potential, is under consideration. Electrons from the conduction band of the source tunnel through the forbidden gap Eg of the channel to the conduction band of the drain. Calculations of the tunneling current J made at helium temperature for the example structures InAs–InAs–InAs, Au–GaSe–Au, and Al–AlN–Al show that for a constant source–drain voltage, VC, of several mV, changes in the gate voltage, VG, applied to the channel within the voltage range of 0–Eg/2e, change J by even 10 orders of magnitude. Unlike existing solutions, such as the tunnel field-effect transistor, the proposed device uses the change of VG (gate voltage), i.e., a change in the electrostatic potential in the channel, to modify the imaginary wave vector kz of tunnel current electrons. Consequently, the gate voltage controls the damping force of the electron wave functions and thus the magnitude of the tunneling current, J. The effect of increasing temperature T on the relation J(VG) is also tested. It is found that only in the structures with a wide forbidden channel gap this effect is insignificant (at least up to T=300 K).